Assistance in Accounting Software Training at the Saraswati Telkom Corpu Gegerkalong Bandung Cooperative - Rizky Shiyammurti, Nastiti; Safira Dewi, Maya; Farman, Fanji (Edumedia Solution, 2026)
The Saraswati Cooperative, located at Telkom Corporate University Gegerkalong, Bandung, faces challenges in managing its financial administration, particularly in recording and reporting, which still uses a manual system. This system leads to data inaccuracies, delays in reconciliation, and difficulties in producing timely and accurate financial reports. Therefore, this community service activity aims to improve the efficiency and accuracy of the cooperative's financial management by providing training and mentoring in the use of cloud-based accounting software, Accurate Online. The method used is a learning-by-doing approach, where participants are directly involved in using the software through transaction simulations relevant to the cooperative's operations. Evaluation results showed significant improvements in three main indicators: basic accounting understanding (60%), mastery of software features (183%), and report analysis skills (87.5%). Although the training went well, there were obstacles such as resistance to technological change from senior staff and inadequate hardware specifications. The implemented solutions included a personal approach to overcome resistance and recommendations for hardware upgrades. The success of this training demonstrates that the use of Accurate Online can accelerate the process of recording and reporting financial data in real time, improve operational efficiency, and support faster and more accurate decision-making at the Saraswati Cooperative. It is recommended that cooperatives conduct regular data maintenance and annual training refreshes to ensure the sustainability and reliability of the new system.